1982
DOI: 10.1139/z82-342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smelter emissions on metal levels in the plumage of ruffed grouse near Sudbury, Ontario, Canada

Abstract: ROSE, G . A., and G . H. PARKER. 1982. Effects of smelter emissions on metal levels in the plumage of ruffed grouse near Sudbury , Ontario, Canada. Can. J . Zool. 60: 2659Zool. 60: -2667 This work investigated geographical and temporal variability in the metal content of the plumage of wild populations of ruffed grouse (Bonasa urnbellus), especially as affected by the emissions of the nickel-copper smelters at Sudbury, Ontario. Levels of copper, nickel, and iron in plumage in the postmoult condition (6, 1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Subsequently, absorbed metals are delivered to target or storage organs or sequestered in feathers (Braune 1987; Lewis and Furness 1991) or other tissues. In some environments, feathers are susceptible to increased metal accumulation by external contamination (Goede and deBruin 1986; Rose and Parker 1982), although such external contamination might be much less in remote areas, and vigorous washing removes significant external contamination.…”
Section: Materials and Analytical Methodsmentioning
confidence: 99%
“…Subsequently, absorbed metals are delivered to target or storage organs or sequestered in feathers (Braune 1987; Lewis and Furness 1991) or other tissues. In some environments, feathers are susceptible to increased metal accumulation by external contamination (Goede and deBruin 1986; Rose and Parker 1982), although such external contamination might be much less in remote areas, and vigorous washing removes significant external contamination.…”
Section: Materials and Analytical Methodsmentioning
confidence: 99%
“…Hg presented a more complex dynamic than Se and Pb, as shown by its additional association with stable isotope signatures and by the differences in levels between sexes. Dissociation between stable isotope signatures and Se or Pb levels could result from stable isotopes being deposited through dietary intake, whereas Se and Pb could have been deposited directly from the atmosphere onto the bird plumage (Rose and Parker 1982;. A number of studies with terrestrial birds reported that Pb levels increase as feathers age or are more exposed than those lying under other plumage (e.g.…”
Section: Differences In Hg Se and Pb Among Colonies And Sexesmentioning
confidence: 99%
“…Rose and Parker (1982) examined the reliability of feathers as an accurate measurement of the accumulation of metals in a bird. Emerging feathers are keratinized and become physiologically isolated from the rest of the bird as they lose vascular and nervous system connections.…”
Section: Bioaccumulationmentioning
confidence: 99%